A (in)constitucionalidade e (in)aplicabilidade das parcerias público-privadas como forma de enfrentamento das crise no sistema prisional brasileiro - Puss, Marina Witter (2024)
This study analyzes the implications of Public-Private Partnerships (PPPs) in the Brazilian prison system, aiming to understand their (un)constitutionality and (in)applicability. The first chapter addresses the historical evolution and conceptual changes of sentences and imprisonments in Brazil, highlighting the influence of social and political factors. The second chapter discusses the integration between public and private sectors in prisons, examining the effects of neoliberalism and comparing national and international models. The third chapter focuses on privatized prison management, assessing its ethical, economic and social consequences and challenging its effectiveness in the rehabilitation and treatment of inmates. In methodological terms, this work adopts an inductive approach, starting from general theories and legislation on incarceration and public-private partnerships to question the viability of administrative contracts in the prison sector. It uses the comparative-functionalist method to examine the relations between the public and private sectors, highlighting differences and similarities in the treatment of prisoners, in addition to analyzing through comparative law the application of the contract modality in foreign countries. The research is based on an extensive bibliographic review, covering doctrinal texts, articles and reports, as well as relevant jurisprudence, to build a solid and diversified argument on the topic. The discussion surrounding privatized prison management is critically inserted into the context of the Research Line on Social Relations and Dimensions of Power, emphasizing the critical analysis of social control and the ethical and constitutional dilemmas arising from the transfer of penal management activities to private entities. In this way, the Brazilian prison crisis is approached from a perspective that transcends the simple question of administrative efficiency, questioning the impacts on individual freedom and constitutional foundations. In conclusion, while PPPs can offer alternative ways to manage the prison system, they should not be seen as the only or the main solution to the crisis faced. The priority must be a profound reform that respects the dignity of prisoners, ensures resocialization as a central objective of sentencing, and strengthens the integrity and effectiveness of the criminal justice system.